Penilaian Tingkat Kesehatan Bank Metode Risk Based Bank Rating dan Depositor Funds BPR Syariah di Indonesia - Nanik Niandari; Evi Grediani; Rahmawati Hanny Yustrianthe (Jurnal Akuntansi, 2019)
This study aims to analyze the bank health level using the risk-based bank rating method against depositors funds. The bank health level is proxied in NPF, PPAP, FDR, ROA, Profit, BOPO, and CAR. The results of this study indicate that PPAP, Profit, BOPO, and CAR show negative and significant influences. Whereas NPF, FDR and ROA show no significant effect on depositor funds. The implications of this study are expected to make BPRS more attention, maintain and improve financial ratios that affect the level of health so that people increasingly believe in placing their funds.